Enraizamento adventício de miniestacas de Mezilaurus itauba - Nicacio, Paulo Roberto (2016)
Despite the extensive exploitation of itaúba, there is still the literature a specific clonal forestry program for the species. The objective of this study was to evaluate the influence of different concentrations of nutrient solution, absence and presence of shading minigarden and influence of plant growth regulator IBA (IBA) in the production and adventitious rooting of cuttings of the species M. Itauba, through technique minicutting. It was set up in minigarden 3 liter polypropylene vessel, with washed sand substrate. The management of mini consisted of nutrient solution fertilization in three concentrations (25%, 50% and 100%) applied being 100 ml per ministump every five days. The mini garden was installed in two rooms, full sun and shade house 50%, to evaluate the influence of shading on productivity and emission shoots of ministumps. survival was evaluated, productivity per square meter per year, minicuttings number by ministumps and length of the longest shoot. The cuttings were collected at present length above 4 cm long, and were taken to rooting. To assess the exogenous application of IBA (IBA) on rooting of cuttings were analyzed two concentrations, 0 (free AIB) and 2,000 mg L-1 of AIB. It was evaluated percentage of rooted cuttings, percentage of cuttings with callus, root number and length of roots. histological analysis of rooted cuttings was carried out to observe the formation of the root and the peg. Survival for minigarden in shady environment showed higher values (82.6%), compared to minigarden in full sunlight (58.3%). The average production of cuttings per square meter per year was 46.4 mini.m2 / year-1 since productivity by the number of cuttings per ministump, there was an average of 1.43 per minicuttings ministump. For the most bud length was no significant effect for the nutrient solution factor, demonstrating a significant difference between the concentration 100% and 25%. Regarding the rooting and number of roots, there was no significant effect for the analyzed variables. Already the percentage of callus was no significant difference between collections of shoots, the third collection with the highest incidence of calluses. For the length of roots, 100% of nutrient solution of the ministumps establishment environment in shade house, the presence of plant growth regulator and the second and third collection, presented higher averages. The results show that the species has the ability to be propagated vegetatively by minicutting technique, the ability to produce epicormic shoots after the break and during the shoot collection and be able to issue roots in cuttings, however, further work may remedy difficulties obtaining superior results in this study for the species.